2020
DOI: 10.1002/suco.202000235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cement additive on physical and mechanical properties of high calcium fly ash geopolymer mortars

Abstract: Geopolymer mortars were produced by replacement of high calcium fly ash with cement at the percentages of 5%, 10%, 15%, 20%, 25%, and 100%. Sodium hydroxide was used as the activator and sodium/binder ratios, by weight, were 10%, 12%, 14%, 16%, 18%, and 20% in mortar mixtures. Some physical properties such as unit weight, water absorption, apparent porosity and ultrasound pulse velocity tests were performed on specimens kept in ambient temperature. Flexural and compressive strength tests were made on specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 33 publications
(51 reference statements)
5
19
0
5
Order By: Relevance
“…It is known that the addition of A in geopolymer production reduces the unit weight [54]. It is similar to the literature that the unit weight increases with the increase in the activator ratio and the increase in the S/A ratio and amount [11,32,57,58,66,67].…”
Section: Unit Weight Test Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…It is known that the addition of A in geopolymer production reduces the unit weight [54]. It is similar to the literature that the unit weight increases with the increase in the activator ratio and the increase in the S/A ratio and amount [11,32,57,58,66,67].…”
Section: Unit Weight Test Resultssupporting
confidence: 79%
“…Similarly, the unit weights increased with the increase in S/Al ratio in the mixture. In some studies, it was stated that the unit weight of the samples increased with the increase in the Na ratio and the increase in the S amount [11,52,58]. Compared to the control samples, it was observed that the unit weights of the samples increased with the increase in the S/A ratio.…”
Section: Unit Weight Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu sebep ile farklı kür koşulları uygulanarak atık cam tozu tabanlı geopolimer harçlara kalsiyum alüminat çimentosu ikamesinin etkisi ortaya konmak için işlenebilirlik, su emme ve boşluk oranı, eğilme dayanımı ve basınç dayanımı deney yöntemleri uygulanmıştır. [20,21,22,23]. KAÇ kullanılarak ortama CaO ilave edilerek N-A-S-H jeli dışında C-A-S-H jeli de oluşumu sağlanmış böylece dayanımda bir miktar iyileştirme yapmıştır [11,22].…”
Section: Introductionunclassified